Islamic Legal Status on Hajj for Transgender People according to Muslim Scholars in North Sulawesi (Mazahib, 2022)
Abstract This study investigates the perceptions of scholars concerning transgender people's legal status on their Hajj ritual validity. In North Sulawesi, seven scholars are considered the opinion-makers and authorities following their understanding of Hajj ritual procedures in Islamic law. The data were analyzed using qualitative methods through interviews and the needs theory by al-Shāṭibī, Ibn Khaldun, and Maslow. The results showed that the gender status of those yet to transition remains original. In contrast, the transitioned transgenders’ status should change to the original law following the court's decision. Second, the scholars approved Hajj rituals for those yet to transition because they had their actual gender and sex. Furthermore, Hajj rituals for transgenders were also legally acceptable in Islamic law following the new status exception by the court. The transgenders' Hajj rituals are valid based on their initial gender or the court's decision. The hajj practices are invalid for those who illegally transition or without court approval. Keywords: Hajj conception, Hajj rituals, transgender people, Ulama in North Sulawesi, Manado.